Design and Data Integration in Mixed Methods Research: Challenges and Ways Forward (Research Nepal Journal of Development Studies, 2018)
Mixed Methods Research (MMR) has been taken as a latest and more practical approach in the field of social science. It has the opportunity of mixing the strengths of both Quantitative (QUAN) and Qualitative (QUAL) methods but has also the challenges of mixing these strengths into the process. The practitioners have been facing the challenge of integrating the design, data sampling, collection, analysis and collection of findings. However, the scholars have proposed multiple ways of conducting the research and coming out from the potential challenges. It explores the conceptual frame and methodological procedures for conducting MMR in the research studies so that the challenges would be illuminated as much as possible. For using any of those typologies, some properties like open-mindedness, aware of methodological corruption and accountable to the stakeholders are essential for a researcher.